Impact of lumbar support on pain reduction in low back pain patients: A systematic review and meta-analysis of randomized control trials - Akbar, Muh. S; Syafar, Muhammad; Thamrin, Yahya; Aras , Djohan; Maidin, Alimin; Arsyad, Muhammad (Narra J, 2025)
Low back pain (LBP) is a global health concern, affecting millions and contributing significantly to disability and economic burden. Various non-pharmacological interventions, including lumbar support, have been explored for LBP management. However, its efficacy remains debated due to inconsistent findings. The aim of this study was to evaluate the impact of lumbar support on pain reduction in individuals with LBP and compare its effectiveness to alternative interventions. A systematic search was conducted across multiple databases (PubMed, ScienceDirect, Scopus, SpringerLink, Google Scholar, and ProQuest) for studies published up to 2023. Data from six search engines were searched using inclusion criteria based on the PICO framework. Search terms included low back pain, lumbar support, lumbar orthose and randomized controlled trial, combined using Boolean operators. Sixteen randomized controlled trials (RCTs) were included in the systematic review, with eight studies analyzed in the meta-analysis. Eligible studies focused on adults with non-specific LBP, assessing pain levels using the Visual Analog Scale (VAS). The meta-analysis was assessed using the standardized mean difference (SMD) in the Visual Analog Scale (VAS). The meta-analysis revealed a statistically significant pain reduction with lumbar support compared to other interventions (SMD: 1.33; 95%CI: -2.09–(-0.57)); p=0.0006), though with high heterogeneity (I²=97%). The findings indicated that lumbar support effectively reduces pain and improves health-related quality of life, particularly in physically demanding occupations or among individuals with severe pain. While efficacy may depend on specific conditions, lumbar support represents a viable non-pharmacological option for LBP management.